Desenvolvimento de um sistema de entrega de 4-nerolidilcatecol baseado em lipossomos elasticos como potencial tratamento contra o câncer de próstata - Guedes, Sabrina Cristina (2023)
The present invention claims the development of natural hybrid formulations composed of liposomes, biosurfactants, and 4-Nerolidylcatechol (4-NC), with antitumor activity. The resulting elastic liposomes were obtained by the lipid film formation technique containing 4-NC, being resuspended in a buffer solution containing biosurfactant and subsequently sonicated for 10 minutes, originating the natural hybrid formulation. This strategy made it possible to design an elastic liposomal system composed exclusively of natural excipients with intrinsic antitumor activity. Furthermore, such systems presented physical-chemical stability for 120 days (4°C) about particle size (nm), polydispersity index, and surface electrical charge (mV). Cytotoxicity studies on human prostate cancer cells revealed a selective antitumor behavior of the nanoformulation, without decreasing the viability of healthy cells. In vivo toxicity tests on chicken embryos demonstrated that the hybrid formulations did not present nanotoxicity in the embryos, not affecting their normal fetal development, determining a safe dose of 2 mg/ml. Furthermore, tumor regression and inhibition tests carried out on the same chicken embryos corroborated the results observed in in vitro cytotoxicity tests, confirming the antitumor activity of the formulation and its effectiveness in reducing and disseminating cancer cells. Histopathological evaluations of tumor tissues from chicken embryos demonstrated significant differences between the treated group and the control group about the pattern of tissue inflammation and the presence and extent of necrotic areas, which are indicative of cell death. Notably, these parameters were more pronounced in the group treated with the elastic liposomal formulation containing 4NC.